Treatment of pulmonary hypertension in idiopathic pulmonary fibrosis: shortfall in efficacy or trial design? - Nathan, Steven D (Dove Medical Press, 2014)
Idiopathic pulmonary fibrosis (IPF) is a disease that carries a high mortality. Pulmonary hypertension (PH) frequently complicates the course of patients with IPF and is associated with significantly worse outcomes. Whether PH is a surrogate or driver of these worse outcomes remains unanswered, but the presence of PH represents an attractive target for therapy. This review delves into the various pulmonary vasoactive agents that have been subjected to study in IPF, the pitfalls of some of these prior studies, and attempts to lay a foundation for future study designs targeting PH in IPF.